Virtual energy storage model of air conditioning loads for providing regulation service. (February 2020) - Ji, Yongli; Xu, Qingshan; Luan, Kaining; Yang, Bin
Abstract: As the pressure of supply–demand balance increases with the high penetration of renewable energy resources, it is widely accepted that demand side resources including air conditioners (ACs) play an important role in providing ancillary services to the grid. In this paper, air conditioning loads are modeled as a kind of virtual energy storage device based on their inherent thermal storage capacity. It is investigated that air conditioning loads can provide regulation service with certain storage power output and ramping rate limits as a result of minimum on/off time requirements. Simulation studies demonstrate the effectiveness of the proposed method by coordinating ACs to track a regulation signal.